Analysis of patient‐specific quality assurance for Elekta Unity adaptive plans using statistical process control methodology. Issue 4 (23rd March 2021) - Strand, Sarah; Boczkowski, Amanda; Smith, Blake; Snyder, Jeffrey E; Hyer, Daniel Ellis; Yaddanapudi, Sridhar; Dunkerley, David A. P.; St‐Aubin, Joel
Abstract: The Elekta Unity MR‐linac utilizes daily magnetic resonance imaging (MRI) for online plan adaptation. In the Unity workflow, adapt to position (ATP) and adapt to shape (ATS) treatment planning options are available which represent a virtual shift or full re‐plan with contour adjustments respectively. Both techniques generate a new intensity modulated radiation therapy (IMRT) treatment plan while the patient lies on the treatment table and thus adapted plans cannot be measured prior to treatment delivery. A statistical process control methodology was used to analyze 512 patient‐specific IMRT QA measurements performed on the MR‐compatible SunNuclear ArcCheck with a gamma criterion of 3%/2 mm using global normalization and a 10% low dose threshold. The lower control limit (LCL) was determined from 68 IMRT reference plan measurements, and a one‐sided process capability ratio ( C p, l ) was used to assess the pass rates from 432 measured ATP and 80 measured ATS plans. Further analysis was performed to assess differences between SBRT or conventional fractionation pass rates and to determine whether there was any correlation between the pass rates and plan complexity. The LCL of the reference plans was determined to be a gamma pass rate of 0.958, and the C p, l of the measured ATP plans and measured ATS plans were determined to be 1.403 and 0.940 for ATP and ATS plans, respectively, while a C p, l of 0.902 and 1.383 was found for SBRT and conventional fractionations respectively. For plan complexity, no correlation was found between modulation degree and gamma pass rate, but a statistically significant correlation was observed between the beam‐averaged aperture area and gamma pass rate. All adaptive plans passed the TG‐218 guidelines, but the ATS and SBRT plans tended to have a smaller beam‐averaged aperture area with slightly lower gamma pass rates.